1988
DOI: 10.3758/bf03208805
|View full text |Cite
|
Sign up to set email alerts
|

Uniqueness of abrupt visual onset in capturing attention

Abstract: Yantis and Jonides (1984) demonstrated that the detection of a target in visual search was markedly enhanced when the target was presented as an abruptly onset character embedded among other characters whose presentation was not characterized by abrupt onset. This effect was attributed to a shift of attention caused by abrupt onset. In the present article, we report experiments investigating whether abrupt onset is simply one member of a large class of stimulus characteristics, all of which are capable of capt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

64
929
13
6

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 896 publications
(1,012 citation statements)
references
References 17 publications
64
929
13
6
Order By: Relevance
“…Derived from this physiological model is the proposal that attentional processing during the feedforward sweep is only affected by physical saliency of the stimulus, whereas stimulus relevance affects selection later, during the recurrent processing stage (Theeuwes, 2010;Van der Stigchel et al, 2009). An argument put forward to favour this proposal is the observation that irrelevant distracters with a unique feature capture attention (Jonides and Yantis, 1988) or gaze (Theeuwes et al, 1999;van Zoest et al, 2004) and elicit electrophysiological responses preceding activity related to processing of the relevant target (Hickey et al, 2006). In contrast, other studies using similar paradigms found that stimulus relevance is a crucial determinant of attentional capture and may affect early cortical processing of visual stimuli (Eimer and Kiss, 2008;Leblanc et al, 2008;Ptak et al, 2011;Yantis and Egeth, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Derived from this physiological model is the proposal that attentional processing during the feedforward sweep is only affected by physical saliency of the stimulus, whereas stimulus relevance affects selection later, during the recurrent processing stage (Theeuwes, 2010;Van der Stigchel et al, 2009). An argument put forward to favour this proposal is the observation that irrelevant distracters with a unique feature capture attention (Jonides and Yantis, 1988) or gaze (Theeuwes et al, 1999;van Zoest et al, 2004) and elicit electrophysiological responses preceding activity related to processing of the relevant target (Hickey et al, 2006). In contrast, other studies using similar paradigms found that stimulus relevance is a crucial determinant of attentional capture and may affect early cortical processing of visual stimuli (Eimer and Kiss, 2008;Leblanc et al, 2008;Ptak et al, 2011;Yantis and Egeth, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Attention tends to be distracted by items that share some perceptual feature with the target (e.g. Jonides and Yantis, 1988). This kind of distraction effect can be thought of as a byproduct of the attempts of voluntary attention to use available visual features to home in on a subset of goal-relevant items in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Most forms of visual search represent the combined influences of bottom-up and top-down attentional control. Jonides and Yantis (1988) proposed that when the top-down information is minimized, not all forms of local salience capture attention. These authors reported that in a conjunction search for letters, the effect of display size on response time (RT) was eliminated when the target letter occurred as an onset singleton (i.e., one letter was presented at a blank location among other letters presented by the removal of lines from figure-8 characters).…”
mentioning
confidence: 99%